Seismic assessment of low ductile RC structures: buildings from before the modern seismic codes. Issue 4 (13th June 2016) - Dias-Oliveira, João; Rodrigues, H; Varum, Humberto
Abstract : Purpose: – When a numerous amount of buildings was built in reinforced concrete, in a period when the regulations did not have the design philosophy for the occurrence of earthquakes, it is of extreme importance to carry out full and effective structural assessments, specially considering and comparing bare frame and infilled structure. The paper aims to discuss these issues. Design/methodology/approach: – Among several possibilities to make the evaluation as, simplified, linear analysis and static non-linear analysis, the non-linear dynamic can provide the most accurate numerical behaviour compared to the real one. The time-history non-linear analyses are developed on the software SeismoStruct for different levels of intensity. Local verifications are then applied separately from both Eurocode and Italian Code. Findings: – The application of validated models for the analysis of real buildings allows a complete seismic assessment. The level of uncertainty increases integrating particularities regarding the infill masonry walls. The paper shows important global and local seismic safety for these complex typology of buildings. Originality/value: – A representative common concrete structure without seismic provisions is first analysed and discussed in terms of global behaviour, deformations and progression of forces. The case study structure is considered both as bare structure and with integrated infill panels. It is also discussed in a local level, about brittle and ductile mechanisms, and extra comparisons between different interpretations of different standards. The case study structure is considered both as bare structure and with integrated infill panels.